Pengaruh Green Marketing Terhadap Kepuasan Pelanggan Produk Kosmetik Merk The Body Shop (Studi pada Mahasiswi Jurusan Manajemen Bisnis di Politeknik Negeri Batam yang Menggunakan Produk Kosmetik Merek The Body Shop) - Shinta Wahyu Hati; Afriani Kartika (Politeknik Negeri Batam, 2015)
This study aims to determine customer satisfaction with products cosmetic from The Body Shop. Cosmetics is something that is closely associated with women. Women use cosmetics to look beautiful every day. There are a lot of cosmetic products sold in the market, but only a few of it are green products. Respondents of this study is the whole student of Business Management in Batam Polytechnic who are consumers of products cosmetic from The Body Shop. The results showed that there was a significant effect product by 0.078 on customer satisfaction. There is a significant effect of 0.414 price to customer satisfaction. There is a significant effect place by 0.775, while there was no significant effect between promotion for -0.070 to customer satisfaction